Characterization of a Novel Natural Filler from Sirisha Bark - Tanmayee Khuntia; Sandhyarani Biswas (Journal of Natural Fibers, 2022)
Nowadays, the search for natural filler to be substituted for synthetic filler providing renewability, eco-friendly, low cost and nontoxic have prompted the researcher to suggest new natural filler reinforced composite materials for structural and automotive application. The bast fibers like sisal, jute, hemp, ramie and flax have already been studied as reinforcements to the polymer composites with enhanced mechanical, thermal and flammability properties. The present study was intended to examine extensively the characteristics of the novel Sirisha bark filler as an alternate novel filler to the polymer composites. The density of the bark filler was found to be 0.713 g/cc. The cellulose, hemicellulose, lignin, moisture and ash content of the filler were found to be 68.23%, 13.26%, 13.25%, 12.66% and 1.82% respectively in comparison to other bark filler. The crystallinity index was calculated to be 65.71% from the X-Ray Diffraction (XRD) analysis. The Thermogravimetric analysis (TGA) study revealed the thermal stability of the Sirisha bark filler to the temperature of 429°C with activation energy of 54.5 kJ/mol. The trace elements like Ca, Al were found to be 1.30% and 2.54% from Energy-dispersive X-ray spectroscopy (EDX).